LANGUAGE VITALITY OF SUNDANESE IN CIANJUR CITY - Kurniawati, Wati; Emzir, Emzir; Akhadiah, Sabarti (Universitas Pendidikan Indonesia, 2021)
Sundanese language usage patterns can cause the ethnic language itself to shift because of switching to using Indonesian in interethnic communication. This study aims to identify language vitality of Sundanese in Cianjur City. Observations focused on language transmission, number and proportion of speakers, domains of use, domains and new media, availability of teaching and literacy materials, and quality of documentation. The formulation of the problem is how the language vitality of Sundanese in Cianjur City? This study uses a qualitative approach with ethnographic methods performed with ethnographic research procedures. The research findings show that the condition of language transmission in children's language acquisition is at an insecure level and the language vitality is decreasing. The condition of the number and proportion of Sundanese speakers is classified as unsafe. The language vitality of Sundanese in the age group 0–14 years is decreasing. The domain of Sundanese language use includes languages that function as multilingual equality and speakers use each language for different functions. The language vitality is decreasing. The condition of the Sundanese domain and new media is dynamic because it is used in the domain of education, employment, broadcast media on television and radio, the internet, and the cyber world. The language vitality is good and could go to the language of science. The condition of Sundanese teaching materials and literacy has a variety of written material and is used as an educational language in schools, but is not used as an administrative language and the vitality of language is good and has the opportunity to go to science and technology. The condition of Sundanese documentation is complete, and the language vitality is good. Therefore, language vitality of Sundanese is decreased in intergenerational transmission indicators needs strengthening.